Strategi Optimalisasi Penggunaan Layanan Mobile Banking Pada PT. Bank Sumut Syariah KCP. Stabat - Ispandi Manurung; Muhammad Saleh; Anjur Perkasa Alam (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine the strategy of the north sumatra bank in optimizing mobile banking services at PT. Bank Sumut Syariah Stabat. This type of research is descriptive research using qualitative methods. The research data is sourced from primary data and secondary data. Data collection techniques in this study used observation, interview and documentation methods. The results of this study show that the strategy of sharia banks in optimizing mobile banking services through several ways and stages, one of which is by issuing an application called